Physiology of soybean plant - Basuchaudhuri, P. (Boca Raton : CRC Press, 2020)
The book provides in-depth knowledge on the physiology of soybean. It is written lucidly, systematically, and in depth. The book provides recent information and findings, explained with illustrations to express the ideas and concepts vividly to university students and researchers, and provides a better understanding of the improvement of the productivity of soybean to cope with the future demand. It describes the physiology of growth, development, flowering, pod development and seed yield as well as C, O, N and Oil metabolisms - their hormonal regulations under normal and stress environmental conditions. Molecular approaches are also described.
OCLC-licensed vendor bibliographic record.
Keywords: Soybean; Soybean -- Physiology; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / Crop Science; TECHNOLOGY / Agriculture / General